PERAN DAN FUNGSI KOMITE ETIK DI RUMAH SAKIT - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article analyses the role and functions of the Hospital Ethics Committee (KERS) as a key pillar of ethical governance in Indonesia’s healthcare system, based on Ministry of Health Regulation No. 42 of 2018, the KODERSI PERSI code of ethics, and national and international journals and books. The role of the KERS is holistic, encompassing that of an educator through bioethics training, a consultant on clinical dilemmas, a monitor of code of conduct compliance, a mediator in disputes, and a policymaker for end-of-life guidelines, whilst its main functions include the management of ethical data, the dissemination of guidelines, the prevention of violations, monitoring and evaluation, and the recommendation of restorative sanctions to the director. The study revealed challenges such as limited independence and human resource constraints; however, KERS’s contributions have been shown to improve service quality, reduce patient complaints, and support KARS accreditation through a preventive-educational approach. Practical implications: hospitals need to strengthen the KERS structure through regular training and digitalisation to ensure a sustainable, humanistic healthcare system.